2007
DOI: 10.1002/ibd.20221
|View full text |Cite
|
Sign up to set email alerts
|

Segmented filamentous bacteria in a defined bacterial cocktail induce intestinal inflammation in SCID mice reconstituted with CD45RBhigh CD4+ T cells

Abstract: Only SFB bacteria together with a defined SPF mixture were effective in triggering intestinal inflammation in the model of IBD in reconstituted SCID mice, while no colitis was detected in GF mice or in mice colonized either with SPF microflora or monoassociated only with SFB or colonized by Bacteroides distasonis + SFB or Fusobacterium mortiferum + SFB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
158
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(171 citation statements)
references
References 42 publications
8
158
1
4
Order By: Relevance
“…Fecal samples from GF mice and swabs from the inner surface of the isolators were cultured under both aerobic and anaerobic conditions, and smears were stained with Gram staining and fluorescence dyes on a weekly basis and before the experiment to verify the continued sterility of the colony. Both GF and SPF BALB/c mice were maintained on a sterile experimental diet (37). GF BALB/c mice were monoassociated at 2 months of age with cultured Lactobacillus plantarum (ATTCC BAA-793, kindly provided by Ursula Wiedermann, Medical University of Vienna) or probiotic E. coli strain Nissle 1917 (Ardeypharm) by gastric gavage.…”
Section: Methodsmentioning
confidence: 99%
“…Fecal samples from GF mice and swabs from the inner surface of the isolators were cultured under both aerobic and anaerobic conditions, and smears were stained with Gram staining and fluorescence dyes on a weekly basis and before the experiment to verify the continued sterility of the colony. Both GF and SPF BALB/c mice were maintained on a sterile experimental diet (37). GF BALB/c mice were monoassociated at 2 months of age with cultured Lactobacillus plantarum (ATTCC BAA-793, kindly provided by Ursula Wiedermann, Medical University of Vienna) or probiotic E. coli strain Nissle 1917 (Ardeypharm) by gastric gavage.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, germ-free mice, mice treated with segmented, filamentous bacteria alone or mice treated with the specific pathogen-free cocktail did not exhibit markers of severe intestinal inflammation. 77 Oral treatment with lysed bacteria may influence the development of experimentally induced intestinal inflammation. We have shown that the severity of dextran sulfate sodium-induced intestinal inflammation in BALB/c mice is reduced by oral administration of a sonicated microbiota containing anaerobic bacteria.…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…Not unexpectedly, then, gastrointestinal microbiota can alter the incidence and severity of gut autoimmune/inflammatory diseases (14,15); in fact, inflammatory bowel disease is "transmissible" via gut-resident microbiota under certain experimental conditions (16). More surprising have been recent observations that SFB's influence can be translated systemically to trigger autoimmune arthritis in a predisposed mouse strain (17) or to exacerbate experimental encephalomyelitis (18).…”
mentioning
confidence: 99%